2019
DOI: 10.1080/26410397.2019.1610279
|View full text |Cite
|
Sign up to set email alerts
|

When political solutions for acute conflict in Yemen seem distant, demand for reproductive health services is immediate: a programme model for resilient family planning and post-abortion care services

Abstract: Ibrahim (2019) When political solutions for acute conflict in Yemen seem distant, demand for reproductive health services is immediate: a programme model for resilient family planning and post-abortion care services,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…The effectiveness of humanitarian public health action depends on knowledge of the context, understanding of priority needs, and correct and timely identification and implementation of the most appropriate interventions [37]. Recent program evaluations in other areas of Yemen have shown that there is continued demand for family planning, maternal and newborn health care and utilization increases when these services are supported by programs and resources [32]. Increasing attention to RMNCAH, particularly reproductive, maternal and newborn health services, requires strategic advocacy within and outside of Yemen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of humanitarian public health action depends on knowledge of the context, understanding of priority needs, and correct and timely identification and implementation of the most appropriate interventions [37]. Recent program evaluations in other areas of Yemen have shown that there is continued demand for family planning, maternal and newborn health care and utilization increases when these services are supported by programs and resources [32]. Increasing attention to RMNCAH, particularly reproductive, maternal and newborn health services, requires strategic advocacy within and outside of Yemen.…”
Section: Discussionmentioning
confidence: 99%
“…Food security and nutrition surveys were conducted in 2014 and 2016, but do not provide information on broader health status or service coverage indicators [27,28]. The few studies published include rigorous analysis of cholera surveillance data, [29,30] a review of health system functionality prior to the escalation of conflict [3], an evaluation of a family planning and post-abortion care program in two governorates, [31,32] and modeling of potential impacts of conflict on health service delivery [33].…”
Section: Introductionmentioning
confidence: 99%
“…4 Some of the most dramatic and direct illustrations of the impact of politics on SRHR and the embodied consequences of those politics can be found in conflict zones and humanitarian settings. Morris et al 5 and Parmar et al 6 explore two very different settings in which the politics of conflict have undermined and violated women's SRHR. Morris et al 5 show how, in Yemen, health facilities have become a primary target for airstrikes and bombing, while the delivery of essential medicines and supplies have been disrupted by blockades.…”
Section: The Embodied Consequences Of Srhr Politicsmentioning
confidence: 99%
“…Morris et al 5 and Parmar et al 6 explore two very different settings in which the politics of conflict have undermined and violated women’s SRHR. Morris et al 5 show how, in Yemen, health facilities have become a primary target for airstrikes and bombing, while the delivery of essential medicines and supplies have been disrupted by blockades. They trace the work of Save the Children to continue with the provision of family planning and post-abortion care programmes within two governorates heavily impacted by the conflict, demonstrating that demand for quality services has continued amidst the crisis.…”
Section: The Embodied Consequences Of Srhr Politicsmentioning
confidence: 99%
See 1 more Smart Citation